Mathematical modelling for sustainable development - Hersh Marion (Berlin Springer-Verlag, 2006)
This book aims at providing both a basic introduction and advanced technical details of some of the available mathematical and computing methods, thus closing the exisiting gap in this field, as well as illustrating their use through case studies and exa
Keywords: Mathematical modelling; Sustainable development